Karakteristik Fisikokimia, dan Sensorik Minuman Probiotik Tepache Kulit Nanas (Ananas Comosus L.) Dengan Variasi Penambahan Kayu Manis (Cinnamomum Verum) dan Cengkeh (Syzygium Aromaticum) - Imam Surya Permana; Ayu Dian Pratiwi Permatahati; Rois Indriawan; Dian Fitriarni; Nurimansyah Nurimansyah (Jurnal Riset, Inovasi, Teknologi & Terapan, 2026)
Tepache is a traditional fermented beverage made from pineapple peel with potential as a functional food. The addition of spices such as cinnamon and cloves is expected to influence the physicochemical and sensory characteristics of the product. This study aimed to examine the effect of spice variation on pH, total soluble solids (°Brix), titratable acidity (TAT), and sensory acceptability of pineapple peel tepache. A completely randomized design (CRD) with three treatments was applied: P1 (control), P2 (cinnamon 3 g/L), and P3 (cinnamon 3 g/L + cloves 1 g/L), each with three replications. Results showed that spice addition significantly affected pH and TAT, but not °Brix. pH increased with spice addition: P1 (3.23), P2 (3.30), and P3 (4.04), while TAT decreased from P1 (0.74%), P2 (0.62%), to P3 (0.51%). °Brix ranged from 8.00 to 9.00 across all treatments. Based on the Friedman Test, the scoring test showed that P3 had the highest mean rank for color, aroma, taste, and viscosity intensity, while the hedonic test showed P1 was preferred in aroma, but P3 was more preferred in taste and overall acceptability. The combination of cinnamon and cloves synergistically inhibited lactic acid bacteria activity, affecting the acid profile of the product; however, further optimization of spice concentration is needed to improve consumer aroma acceptance.